Neanderthal had a “crush” on fats. Macronutrient estimation in Middle Paleolithic (Late Mousterian) hunter-gatherers of southern Italy - Crezzini, Jacopo; Modi, Alessandra; Cannariato, Costanza; Caramelli, David; Ronchitelli, Annamaria; Boscato, Paolo; Moroni, Adriana; Boschin, Francesco (Frontiers in Environmental Archaeology, 2025)
During the Late Mousterian period Apulia (southeastern Italy) was characterized by frequent and prolonged aridity that could have caused the scarcity of vegetable foods and, consequently, a lack of important nutritional compounds. Zooarchaeological studies from several Mousterian contexts show that Apulian Neanderthals may have responded to this crisis by increasing the exploitation of ungulates. In particular, bone grease rendering was likely one of the dominant activities conducted on-site. Anthropologists and nutritionists have long recognized that the diets of modern-day hunter-gatherers may represent a reference standard for human nutrition in the past and a model for their adaptation to specific environmental conditions. In addition, evaluating of certain qualitative and quantitative aspects of the animal/plant nutrient intake and absorption may provide important information regarding the nutritional needs and the physiology of these human groups. In this analysis, we combine ethnographic data related to animal economic subsistence patterns of hunter-gatherers, zooarchaeological data from Late Mousterian assemblages located in Apulia, the physiology of medium-large ungulates, as well as new paleo genomic analyses of Neanderthals and modern humans. Analyzing and displaying multiple sources of information allowed us to quantify a low daily energy intake from carbohydrates for Late Mousterian populations in southern Italy, in contrast to a surplus of animal protein and fats, obtained from the specific treatment of carcasses inferred from the zooarchaeological data.